Organic and inorganic fertilizers modulate the response of the soil microbiome to salinity stress - Malal, Halima; Garcia, Joshua A.; Marrs, Anna; Ait Hamza, Mohamed; Emerson, Courtney; Nocco, Mallika; Lakhtar, Hicham; Lazcano, Cristina (Frontiers in Microbiology, 2025)
Salinity stress threatens soil microbiomes, a key driver of soil multifunctionality and health. This study employed high-throughput sequencing of 16S rRNA, PLFAs, multifunctionality index, and co-occurrence networks to gain a comprehensive understanding of the dynamic responses of soil microbiomes to salinity stress gradient (0, 0.4 and 1 mol NaCl). Additionally, we investigated how these responses are shaped by the addition of vermicompost and NPK fertilizer during short-term (2-h) and long-term (70-day) incubation periods. Salinity stress reduced bacterial and fungal phospholipid fatty acids (PLFA) concentrations in the short-term. Over the long-term, the microbial community evolved into a new pattern under salt stress, favoring the presence of Bacteriodota, a salt-tolerant phylum, while decreasing the relative abundance of Acidobacteriota and Planctomycetota, which are more salt-sensitive. Furthermore, salinity decreased species richness by 11.33% and soil multifunctionality by 21.48% but increased microbial network complexity while decreasing its stability. Incorporating vermicompost increased bacterial and fungal PLFAs, enhanced bacterial diversity by 2.33%, promoted salt-tolerant bacteria, and increased the complexity and stability of the bacterial network. Conversely, the application of NPK fertilizer reduced bacterial richness, alpha diversity and soil multifunctionality by 14.52, 5.83, and 12.34%, respectively, further disrupting the microbial community and making resilience to salinity stress more challenging. Furthermore, NPK fertilization increased bacterial network complexity but decreased its stability. This study underscores the significance of employing vermicompost to improve the health of saline soils. Furthermore, it emphasizes the negative impacts of NPK fertilizer on soil microbial structure and function and hinder its recovery from salinity’s impacts.